2000
DOI: 10.14507/epaa.v8n8.2000
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in Dual Language Practice

Abstract: The capacity for dual-language programs to deliver specific benefits to students with different primary and secondary language skills continues to be debated. Individuals favoring dual language assert that as it relies upon a reciprocal approach, dual language students acquire dual language proficiency without the need for teachers to translate from one language to another. By utilizing and conserving the language skills that students bring, dual language students also gain cross-cultural understandings and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(2 citation statements)
references
References 8 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Another related challenge noted in studies is the risk of uneven language development. Not surprisingly, a number of researchers find that there are many more English language curricular resources than there are resources in Spanish (Amrein & Peña, 2000). Also, because state standardized tests tend to be in English, teachers often spent more time prioritizing instruction in English to help students be in a better position to score highly on such tests (Alanís, 2000).…”
Section: Continuing Challenges Of Two-way Immersionmentioning
confidence: 99%
“…Another related challenge noted in studies is the risk of uneven language development. Not surprisingly, a number of researchers find that there are many more English language curricular resources than there are resources in Spanish (Amrein & Peña, 2000). Also, because state standardized tests tend to be in English, teachers often spent more time prioritizing instruction in English to help students be in a better position to score highly on such tests (Alanís, 2000).…”
Section: Continuing Challenges Of Two-way Immersionmentioning
confidence: 99%
“…For example, a growing number of DLBE programs across the nation have marketed and structured their programs to serve predominately White, middle-class students, limiting access for emergent bilinguals who are still developing English skills (Boyle et al, 2015; Valdez et al, 2016). For CLD students who have access to DLBE programs, scholars have still found that programs may allocate disproportionate value, time, and resources to the instruction and support of the English language and dominant culture (Amrein & Peña, 2000; Cervantes-Soon et al, 2017; de Jong & Howard, 2009; Flores & García, 2017).…”
Section: Introduction To the Problem And Purpose Of The Studymentioning
confidence: 99%